2019
DOI: 10.1111/jns.12305
|View full text |Cite
|
Sign up to set email alerts
|

Mutational screening of the SH3TC2 gene in Greek patients with suspected demyelinating recessive Charcot‐Marie‐Tooth disease reveals a varied and unusual phenotypic spectrum

Abstract: Charcot‐Marie‐Tooth disease type 4 C (CMT4C) is an autosomal recessive form of demyelinating peripheral neuropathy caused by mutations in SH3TC2, characterized by early onset, spine deformities, and cranial nerve involvement. We screened SH3TC2 in 50 unrelated Greek patients with suspected demyelinating Charcot‐Marie‐Tooth disease and pedigree compatible with recessive inheritance. All patients had been previously screened for PMP22, GJB1, and MPZ mutations. We found five previously identified pathogenic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…These mutations include nonsense, splice-site, and frameshift mutations, either in homozygous or compound heterozygous states, and they lead to the premature termination of protein synthesis or the production of nonfunctional proteins. Some missense mutations, such as E657K, R1109P, and R648W, have also been observed (1,2,11). In our study, 3 previously reported nonsense mutations (E553 * , R904 * , and R954 * ) (1, 10, 12), 4 novel splicing mutations (c.280…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These mutations include nonsense, splice-site, and frameshift mutations, either in homozygous or compound heterozygous states, and they lead to the premature termination of protein synthesis or the production of nonfunctional proteins. Some missense mutations, such as E657K, R1109P, and R648W, have also been observed (1,2,11). In our study, 3 previously reported nonsense mutations (E553 * , R904 * , and R954 * ) (1, 10, 12), 4 novel splicing mutations (c.280…”
Section: Discussionsupporting
confidence: 69%
“…In a Southern Italy study, the prevalence of SH3TC2 in overall CMT population was 3.2%, but it raised at 11.6% in sporadic demyelinating CMT cohort (SH3TC2 represents the second prevalent gene in this selected population) (15). The R954 * mutation, which is located in exon 11, has been reported to be particularly prevalent in central Europe, the Mediterranean basin, and the USA (1,3,5,11,(15)(16)(17)(18). This mutation has been identified in more than half or nearly all of the patients in English, French, Greek, Norwegian and Czech cohorts (3,11,(16)(17)(18), whereas none of the patients in Japanese and Korean cohorts had reported the mutation (6, 7).…”
Section: Discussionmentioning
confidence: 98%
“…Cranial nerve involvement is another key point of CMT4C, as it is shown in our study with eight patients reporting HL and one patient with increased latencies of visual brainstem responses. Recently, Kontogeorgiou et al reported cranial nerve involvement in 31% of the cases [7], and Yger et al in a French cohort in 71% [4]. HL is the foremost observed condition [8].…”
Section: Resultsmentioning
confidence: 94%
“…2,4 Furthermore, multiple phenotypes besides limb weakness or vibration-dominant sensory symptoms were identified; namely, deafness, diplopia, nystagmus, facial sensory loss, trigeminal neuralgia, cerebellar ataxia, and scoliosis. 1,2,4 To compare with reported typical patients, our patient presented with a mild phenotype. He did not show spine deformity, atrophy, or cranial nerve involvement, with CMTNS and distal weakness scores of 9 and 4, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Loss of functional SH3TC2 protein widens Ranvier nodes and thinning of myelin sheaths result in slow conduction velocity. 1 Law and tradition have prohibited consanguineous marriage in Korea. Therefore, the prevalence of autosomal recessive (AR) disease is relatively low and reported patients with CMT4C harbor compound heterozygote mutations in the SH3TC2.…”
Section: Introductionmentioning
confidence: 99%